Targeted radionuclide therapy and diagnostic imaging of SSTR positive neuroendocrine tumors: a clinical update in the new decade - Haugh, Katherine N.; Sanwick, Alexis M.; Chaple, Ivis F. (Frontiers in Nuclear Medicine, 2025)
Neuroendocrine tumors (NETs) are a heterogeneous group of neoplasms characterized by their overexpression of somatostatin receptors (SSTRs), which can be utilized for peptide receptor radionuclide therapy. This review provides a comprehensive update on the clinical trials of radiolabeled SSTR-targeting radiopharmaceuticals since 2020, with a focus on somatostatin receptor agonists and antagonists radiolabeled with 68Ga, 18F, 99mTc, 177Lu, 161Tb, 212Pb, 67Cu, and 225Ac. Head-to-head clinical trials demonstrate that radiolabeled SSTR antagonists such as [68Ga]Ga-DOTA-JR11 and [68Ga]Ga-DOTA-LM3 offer improved lesion detection and tumor-to-background ratios (particularly in liver metastases) compared to radiolabeled agonists like [68Ga]Ga-DOTA-TOC and [64Cu]Cu-DOTA-TATE. Additionally, 18F-labeled agents offer logistical and dosimetric advantages over 68Ga, due to 18F's longer half-life and cyclotron production, allowing for delayed imaging and increased availability to a wider range of patients. Emerging targeted alpha therapy agents, including [225Ac]Ac-DOTA-TATE, show promising results in treating disease resistant to conventional therapies due to the high linear energy transfer of alpha particles, which leads to improved localized cytotoxicity. Collectively, these developments support a shift toward more precise, receptor-specific theragnostics, emphasizing the need for further head-to-head clinical trials and integration of dosimetry-driven, personalized treatment planning in the management of NETs.